The Effect Of Audit Committee On Financial Performance Of Listed Companies In Jordan: The Moderating Effect Of Enterprise Risk Management. - Saddam Ali Shatnawi; Mustafa Mohd Hanefah; Monther Eldaia; Ahmad Marei; Saad Alaaraj (Allied Business Academies, 2024)
Non-Indexed Publication